Why and in what sense do conference interpreters need special software? - Rütten, Anja (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Information society, digitalisation, software solutions for everybody. Also for conference interpreters? What are the special characteristics of an inter-preter’s workflow that require specialised software? Does this specialised software already exist? After having a look at scientific findings and existing solutions in this field, this article shows the differences between the software requirements of interpreters and those of translators or terminologists. On the basis of these considerations, a model for a special software solution for conference interpreters is presented.